2020
DOI: 10.1016/j.molcel.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Restricted Regulation of SCD and Fatty Acid Saturation by MITF Controls Melanoma Phenotypic Plasticity

Abstract: Phenotypic and metabolic heterogeneity within tumors is a major barrier to effective cancer therapy. Yet how metabolism is implicated in specific phenotypes, and whether lineage-restricted mechanisms control key metabolic vulnerabilities remains poorly understood. In melanoma, down-regulation of the lineage addiction oncogene Microphthalmia-associated Transcription Factor (MITF) is a hallmark of the proliferative-to-invasive phenotype switch, though how MITF promotes proliferation and suppresses invasion is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 116 publications
3
117
0
Order By: Relevance
“…As we have identified ATF4 as the responsible transcription factor for PTGS2 induction downstream of NRF2, it is likely that an interaction between ATF4 and MITF regulates PTGS2 in melanoma cells. In support of this theory, it was previously reported that MITF increases the ratio between monounsaturated and saturated fatty acids, which can negatively impact ATF4 [45]. As ATF4 also suppresses MITF levels [8], both are connected by a mutually negative regulatory loop.…”
Section: Discussionmentioning
confidence: 70%
“…As we have identified ATF4 as the responsible transcription factor for PTGS2 induction downstream of NRF2, it is likely that an interaction between ATF4 and MITF regulates PTGS2 in melanoma cells. In support of this theory, it was previously reported that MITF increases the ratio between monounsaturated and saturated fatty acids, which can negatively impact ATF4 [45]. As ATF4 also suppresses MITF levels [8], both are connected by a mutually negative regulatory loop.…”
Section: Discussionmentioning
confidence: 70%
“…Primary tumors may acquire functional mutations during tumor development that initiate the invasion‐metastatic cascade whereby cancer cells adopt an epithelial‐to‐mesenchymal (EMT) phenotype to disseminate from primary lesions into circulation (Lu & Kang, ; Vivas‐García et al , ). Once cancer cells leave the primary tumor and embark on this journey, they must undoubtedly adapt their metabolism to overcome the stresses and dangers they face in circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other fatty acids, sapienate is only found in humans and is a major component of human sebum 78 . Intriguingly, a recent study indicated that SCD expression is positively regulated by MITF 79 . Therefore, one potential mechanism of increased dependency on FADS2-mediated fatty acid desaturation in MITF low /AXL high LD-rich melanoma cell lines could be via MITF.…”
Section: Discussionmentioning
confidence: 99%